Economic advice and executive policy; Recommendations from past members of the council of economic advisers - "Sichel, Werner ed." (New York, 1978)
This book contains following topics: Introduction; An Elder Statesman's advice to a CEA Chairman; Economic Problems and economic Advice: A Half- Century of Evolution; The Breakdown of Bretton Woods; Current Policy in a long-tern context; The search for the Grail: Economic Policy Issues of the Late 1970s; Full recovery of stagnation?
Keywords: United States - Economic policy - 1945 - 1960